There or not there? A multidisciplinary review and research agenda on the impact of transparent barriers on human perception, action, and social behavior - Marquardt, Gesine; Cross, Emily S.; De Sousa, Alexandra A.; Edelstein, Eve; Farne, Alessandro; Leszczynski, Marcin; Patterson, Miles; Quadflieg, Susanne (Frontiers in Psychology, 2015)
Through advances in production and treatment technologies, transparent glass has become an increasingly versatile material and a global hallmark of modern architecture. In the shape of invisible barriers, it defines spaces while simultaneously shaping their lighting, noise, and climate conditions. Despite these unique architectural qualities, little is known regarding the human experience with glass barriers. Is a material that has been described as being simultaneously there and not there from an architectural perspective, actually there and/or not there from perceptual, behavioral, and social points of view? In this article, we review systematic observations and experimental studies that explore the impact of transparent barriers on human cognition and action. In doing so, the importance of empirical and multidisciplinary approaches to inform the use of glass in contemporary architecture is highlighted and key questions for future inquiry are identified.